Safety and efficacy of remote ischemic conditioning for the treatment of intracerebral hemorrhage: A proof-of-concept randomized controlled trial. Issue 4 (April 2022) - Zhao, Wenbo; Jiang, Fang; Li, Sijie; Liu, Guiyou; Wu, Chuanjie; Wang, Yuang; Ren, Changhong; Zhang, Jing; Gu, Fei; Zhang, Quanzhong; Gao, Xinjing; Gao, Zongen; et al.
Background: Remote ischemic conditioning can promote hematoma resolution, attenuate brain edema, and improve neurological recovery in animal models of intracerebral hemorrhage. Aims: This study aimed to evaluate the safety and preliminary efficacy of remote ischemic conditioning in patients with intracerebral hemorrhage. Methods: In this multicenter, randomized, controlled trial, 40 subjects with supratentorial intracerebral hemorrhage presenting within 24–48 h of onset were randomly assigned to receive medical therapy plus remote ischemic conditioning for consecutive seven days or medical therapy alone. The primary safety outcome was neurological deterioration within seven days of enrollment, and the primary efficacy outcome was the changes of hematoma volume on CT images. Other outcomes included hematoma resolution rate at 7 days ([hematoma volume at 7 days − hematoma volume at baseline]/hematoma volume at baseline), perihematomal edema (PHE), and functional outcome at 90 days. Results: The mean age was 59.3 ± 11.7 years and hematoma volume was 13.9 ± 4.5 mL. No subjects experienced neurological deterioration within seven days of enrollment, and no subject died or experienced remote ischemic conditioning-associated adverse events during the study period. At baseline, the hematoma volumes were 14.19 ± 5.07 mL in the control group and 13.55 ± 3.99 mL in the remote ischemic conditioning group, and they were 8.54 ± 3.99 mL and 6.95 ± 2.71 mL at seven days after enrollment, respectively, which is not a significant difference ( p  > 0.05 each). The hematoma resolution rate in the remote ischemic conditioning group (49.25 ± 9.17%) was significantly higher than in the control group (41.92 ± 9.14%; MD, 7.3%; 95% CI, 1.51–13.16%; p  = 0.015). The absolute PHE volume was 17.27 ± 8.34 mL in the control group and 12.92 ± 7.30 mL in the remote ischemic conditioning group at seven days after enrollment, which is not a significant between-group difference ( p  = 0.087), but the relative PHE in the remote ischemic conditioning group (1.77 ± 0.39) was significantly lower than in the control group (2.02 ± 0.27; MD, 0.25; 95% CI, 0.39–0.47; p  = 0.023). At 90-day follow-up, 13 subjects (65%) in the remote ischemic conditioning group and 12 subjects (60%) in the control group achieved favorable functional outcomes (modified Rankin Scale score ≤ 3), which is not a significant between-group difference ( p  = 0.744). Conclusions: Repeated daily remote ischemic conditioning for consecutive seven days was safe and well tolerated in patients with intracerebral hemorrhage, and it may be able to improve hematoma resolution rate and reduce relative PHE. However, the effects of remote ischemic conditioning on the absolute hematoma and PHE volume and functional outcomes in this patient population need further investigations. Clinical Trial Registration URL: http://www.clinicaltrials.gov . Unique identifier: NCT03930940.